Herbicidal activities of wheat residues in transplant Aman rice (Progressive Agriculture, 2018)
Allelopathic potentiality of crop residues may be helpful to minimize the serious problems in the present agricultural production such as environmental pollution, unsafe products, human health concerns, depletion of crop diversity, soil sickness and reduction of crop productivity. In this phenomenon an experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during June to November, 2015 to evaluate the effect of crop residues of wheat on weed management and crop performance of T. Aman rice. The experiment consisted of three varieties (cv. BRRI dhan32, BRRI dhan33 and BRRI dhan49) and five different treatments (viz. no crop residues, wheat crop residues @ 0.5, 1.0, 1.5 and 2.0 t ha-1). The experiment was laid out in a randomized complete block design with three replications. Five weed species belonging to three families infested the experimental plots. Weed population, weed dry weight and percent inhibition of weed were significantly influenced by wheat crop residues and cultivar. The maximum weed growth was noticed where no crop residues was incorporated and the minimum was found where @ 2.0 tha-1 wheat crop residues was incorporated. The grain yield as well as the other yield contributing characters produced in BRRI dhan49 was the highest among the studied varieties. The highest percent inhibition of 75.32, 58.24, 72.60, 57.45 and 82.24 was in Shama, Panishapla, Pani chaise, Panikachu and Susnishak, respectively which was caused by the application of wheat crop residues @ 2 t ha-1. The highest loss of grain yield was obtained where no crop residues were incorporated. The highest numbers of tillers hill-1, numbers of grains panicle-1, 1000-grain weight, grain yield, straw yield were observed where wheat crop residues were incorporated @ 2.0 t ha-1. The results of this study indicate that different amount of wheat crop residues showed potential activity to suppress weed growth.Progressive Agriculture 28 (4): 253-261, 2017